Familial Aggregation of Childhood‐ and Adulthood‐Onset Systemic Lupus Erythematosus. Issue 8 (11th June 2020) - Sinicato, Nailú Angélica; de Oliveira, Luciana; Lapa, AlineTamires; Postal, Mariana; Peliçari, Karinade Oliveira; Costallat, Lilian T. L.; Marini, Roberto; Gil‐da‐Silva‐Lopes, Vera Lúcia; Niewold, Timothy B.; Appenzeller, Simone
Abstract : Objective: To assess the familial occurrence of systemic lupus erythematosus (SLE) in a large Brazilian cohort. Methods: Consecutive patients with SLE were recruited and stratified according to age at disease onset into childhood‐onset SLE or adult‐onset SLE. Each patient was personally interviewed regarding the history of SLE across 3 generations (first‐, second‐, and third‐degree relatives). Recurrence rates were analyzed for each degree of relation. Results: We included 392 patients with SLE (112 with childhood‐onset SLE and 280 with adult‐onset SLE). We identified 2, 574 first‐degree relatives, 5, 490 second‐degree relatives, and 6, 805 third‐degree relatives. In the combined overall SLE cohort, we observed a familial SLE recurrence rate of 19.4 in first‐degree relatives, 5.4 in second‐degree relatives, and 3.0 in third‐degree relatives. Recurrence rates were higher for first‐ and second‐degree relatives of patients with childhood‐onset SLE than for first‐ and second‐degree relatives of patients with adult‐onset SLE (25.2 versus 18.4 for first‐degree, and 8.5 versus 4.5 for second‐degree), while in third‐degree relatives, recurrence rates were higher in adult‐onset SLE than in childhood‐onset SLE ( P = 2.2 × 10 –4 for differences in recurrence proportions between childhood‐onset SLE and adult‐onset SLE). There were no phenotypic differences in patients from multicase versus single‐case families, and there was no sex‐skewing observed in the offspring of patients with SLE. Conclusion: The greater decline in SLE recurrence rate by generation in childhood‐onset SLE versus adult‐onset SLE suggests a more polygenic and epistatic inheritance and suggests that adult‐onset SLE may be characterized by fewer risk factors that are individually stronger. This finding suggests a higher genetic load in childhood‐onset SLE versus adult‐onset SLE and a difference in the genetic architecture of the disease based on age at onset.